Observing landscape changes around the Nicosia old town center using multi-temporal datasets - Cuca, Branka; Agapiou, Athos; Hadjimitsis, Diofantos G. (My University, 2016)
In 1980s a significant boom in construction industry was witnessed in Cyprus. This paper explores the changes of land use that have occurred over the past 30 years around the historical capital of Nicosia, in particular around the core of the historic city defined by the Venetian walls. Further to some Open geospatial Data available within the national and regional geo-portals, the research has focused on the use and exploitation of freely accessible satellite imagery (such as Landsat and Sentinel imagery) and other archive aerial datasets in order to observe the most recent modifications of the urban landscapes. The changes occurred over time were observed using multi-spectral multi-temporal dataset with main aim to create thematic maps for further interpretation. The changes were hence identified, mapped and structured so as to emphasise different types and density of urban development affecting the surrounding landscapes and potential “hot-spots”. Such observations could be a valuable input to the future urban development of Nicosia.
Keywords: Changing landscape; Cyprus; Earth observation; Historical cities; Landsat; Nicosia